Surgical treatment of patients with cerebral metastases in the motor area - D. M. Belov; V. B. Karakhan; A. Кh. Bekyashev; N. V. Sevyan; V. A. Aleshin; A. A. Mitrofanov; E. V. Prozorenko; D. V. Sashin; N. V. Garanina (Опухоли головы и шеи, 2022)
Introduction. The surgical stage takes an important place in the complex treatment of patients with cerebral metastases of malignant tumors. In general, all efforts during surgical intervention should be aimed at restoring a good functional status, since severe neurological symptoms can deprive patients of the opportunity to continue complex treatment, which will negatively affect overall survival. The most pronounced neurological symptoms are observed in patients with metastases in the motor area. In this article, we tried to substantiate the need for surgery of cerebral metastases in patients with severe motor deficits, evaluate the results of surgical treatment and also to develop optimal surgical removal techniques.The study object – to assess the effectiveness of surgical removal of metastases in the motor cortex by evaluating the dynamics of motor function recovery and regression of paroxysmal symptoms.Materials and methods. An analysis of the surgical treatment of 18 patients with metastases in the motor area was carried out. Tumor localization was verified using magnetic resonance imaging, before surgery, neuronavigation system Brainlab during surgery. Мagnetic resonance tractography made it possible to assess the localization and degree of compression of the fibers of the cortico-spinal tract. Functional monitoring was not performed during the operation. The operations were performed using a ZEISS OPMI PENTERO 800 microscope.Results. Recovery of motor function after surgery was noted in 17 (94.5 %) cases. It was complete or partial. With metastases of a solid, solid-necrotic, solid-cystic structure, regression of pyramidal symptoms developed gradually, starting from 4 days after surgery. As a rule, rehabilitation therapy (therapeutic exercise, massage, electromyostimulation) is carried out on patients from 3 days after surgery, which accelerated the recovery process. The maximum effect developed on the 15th day after the operation. Faster recovery of motor function was observed in patients with large cystic metastases who underwent surgery in the volume of Ommaya reservoir implantation. They began to recover motor function a few hours after awakening. Regression of paroxysmal symptoms was noted in all cases. Although the patients continued to take anticonvulsants. The observation period was 6 months.Сonclusion. Surgical removal of cerebral metastases in the motor area allows achieving complete or partial regression of neurological symptoms. At the same time, the recovery period is short – from several hours to 14 days. It becomes possible to cancel glucocorticoids 7–10 days after the operation. Conditions are being created for the continuation of complex treatment of patients previously considered incurable.